Peran Keluarga dalam Penguatan Moderasi Beragama untuk Pemantapan Empat Pilar Kebangsaan - Badrun Hasani (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study was to determine the role of the family in strengthening religious moderation for strengthening the four pillars of nationality. This study uses a qualitative descriptive method by describing theories that are relevant to the variables studied. The results of the study show that religious moderation needs to be taught to children from an early age so that they understand how to deal with differences between religious communities, radicalism, Pancasila values, so that in the end the children will grow into individuals who respect each other, tolerate, and do not impose their will because they have been framed with noble character (Akhlakul Karimah). The conclusion of the research that starting from a small family is the first madrasah for children which is a candidate for the next generation of the nation who loves peace and harmony to realize Islam rahmatan lil'alamin, always teaches and implements exemplary which is reflected in good behavior, noble and civilized, as well as teaching Islamic values which highly uphold human dignity and worth, respecting differences, mutual affection, mutual help and other noble morals. Keywords: Diverse Moderatio, Noble Morals, Religious Education in the Family